Periodontal status of patient’s underwent hemodialysis therapy - Jenabian, Niloofar (Babol University of Medical Sciences, 2013)
Background: Chronic renal failure patients undergoing hemodialysis are susceptible to periodontal diseases due to systemic complications of the disease and using different drugs. The present study investigated the periodontal status of patient’s who underwent hemodialysis, in Babol, northern Iran. Methods: One-hundred-fifteen hemodialysis patients (63 males, 52 females) with the mean age of 47.9±15.3 years were studied at Shahid Beheshti Hospital in Babol, Iran. Periodontal parameters including plaque index (PI), gingival index (GI), clinical attachment level (CAL) and probing pocket depth (PPD) were measured in these patients. The data were collected and analyzed. Results: The PI, GI, CAL and PPD were 2.37±0.55, 2.36±0.63, 3.98±1.61 and 4.41±1.4, respectively. Significant positive correlations were found between the participants’ age and PI (p<0.024) and p<0.001, respectively. Also, CAL was significantly higher in males than females (4.39±1.57 vs. 3.53±1.56, p<0.02). Conclusion: The results show that longer duration of hemodialysis is associated with severe periodontal diseases, especially in males.